Pengaruh perendaman dengan red wine terhadap perubahan warna restorasi resin komposit one shade - Priscilia Dinata Tobing, Fiona; Ongki Iskandar, Bernard; Stefani, Rosita (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: The very rapid development of technology for aesthetic treatment results has given rise to composite resin namely one shade composite resin. One shade composite resin has a chameleon effect that can copy all tooth colors using just one color. However, this composite resin can change color which causes patient dissatisfaction with the treatment results because it interferes with aesthetic value and appearance. This color change is influenced by the presence of color pigments and the acidic pH in the food and drinks, specifically red wine. Objective: To examine the effect of red wine consumption on the color stability of one shade composite resin. Methods: This research used sixteen one shade composite resins, consisting of 2 different brands in cylindrical shape (diameter: 10 mm; height: 2 mm) and allocated to 2 different groups, that is the control and treatment groups for each type of composite resin. Control groups were immersed in artificial saliva fo 6 days within 144 hours. Treatment groups were immersed in red wine for 4 days within 96 hours, followed by immersion in artificial saliva for 2 days within 48 hours. Color measurements were measured using vita easyshade V. Results: The ANOVA Two Way results showed that there were significant color change (p<0,05). Conclusion: There is an effect of immersion red wine on the color stability of one shade composite resin.